Comparison of Digestive Enzyme Activities and Expression of Small Intestinal Transporter Genes in Jinhua and Landrace Pigs - Liu, Xiuting; Lyu, Wentao; Liu, Lei; Lv, Kaikai; Zheng, Fen; Wang, Yuanxia; Chen, Jinggang; Dai, Bing; Yang, Hua; Xiao, Yingping (Frontiers in Physiology, 2021)
Digestive enzyme activity is involved in the regulation of growth performance because digestive enzymes function to improve the feed efficiency by digestion and in turn to modulate the process of nutrient metabolism. The objective of this study was to investigate the differences of the digestive enzyme activities and expression of nutrient transporters in the intestinal tract between Jinhua and Landrace pigs and to explore the potential breed-specificity in digestion and absorption. The pancreas segments and the digesta and mucosa of the duodenum, jejunum, and ileum were collected from 10 Jinhua pigs and Landrace pigs, respectively. The activities of trypsin, chymotrypsin, amylase, maltase, sucrase, and lipase were measured and the expression levels of PepT1, GLUT2, SGLT1, FABP1, FABP2, and FABP4 were examined. Results showed that the trypsin activity in the pancreas of Jinhua pigs was higher than that in Landrace pigs, but was lower in the small intestine, except for in the jejunal mucosa. The chymotrypsin activity in the small intestine of Jinhua pigs was higher than that in Landrace pigs, except for in jejunal mucosa and contents. Compared with Landrace pigs, the amylase and maltase activity in the small intestine of Jinhua pigs was lower, except for in ileal mucosa. The sucrase activity in the small intestine of Jinhua pigs was also lower than Landrace pigs, except for in jejunal mucosa. Furthermore, the lipase activity in the small intestine of Jinhua pigs was higher than that in Landrace pigs. The mRNA levels of PepT1 and GLUT2 in duodenal, jejunal and ileal mucosa showed no difference between Jinhua and Landrace pigs, whereas SGLT1 in ileal mucosa was lower in Jinhua pigs. The mRNA levels of FABP1, FABP2 and FABP4 in the small intestinal mucosa of Jinhua pigs were higher than in Landrace pigs. These findings indicate that there is a certain difference in the digestibility and absorption of nutrients in small intestine of Jinhua and Landrace pigs, partially resulting in their differences in growth development and fat deposition.